The Production of African Print Fabric Designs: A User-Centric Design Approach - Adeloye, Adebayo Abiodun; Akinbogun, Tolulope Lawrence; Ogunduyile, Sunday Roberts (Prithvi Academic Journal, 2023)
African print fabric is a major textile item in Africa because of its high economic value. This study focused on the production of African print fabrics that are user-centered. The textile industry in Nigeria is presently in a comatose state and there is a need to develop a design model for producing textile designs that will meet the specific needs of the target consumers. The practice-led and survey research designs were adopted for the study. The study population comprised the users of African print fabrics in Southwest Nigeria. Since the users of the fabrics are infinite, the Cochran formula was used to calculate the sample size for the study. 384 users were sampled using the open-ended questionnaires and opinion sampling for data collection. The data were analyzed using the simple descriptive statistical tools such as frequency and percentage. The study revealed that the African print fabric users across different age groups have specific preferences for African print fabrics. It was therefore recommended that the textile designers focus on producing the user-centered African print fabrics that meet the specific needs of consumers.